2015
DOI: 10.1039/c4cs00486h
|View full text |Cite
|
Sign up to set email alerts
|

Nanodiamonds and silicon quantum dots: ultrastable and biocompatible luminescent nanoprobes for long-term bioimaging

Abstract: Fluorescence bioimaging is a powerful, versatile, method for investigating, both in vivo and in vitro, the complex structures and functions of living organisms in real time and space, also using super-resolution techniques. Being poorly invasive, fluorescence bioimaging is suitable for long-term observation of biological processes. Long-term detection is partially prevented by photobleaching of organic fluorescent probes. Semiconductor quantum dots, in contrast, are ultrastable, fluorescent contrast agents det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
133
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(143 citation statements)
references
References 356 publications
0
133
0
1
Order By: Relevance
“…An important advantage of silicon quantum dots (SiQDs) is that, unlike other elements, silicon is biocompatible. Consequently, SiQDs can be used in hot research fields of nanomedicine, such as fluorescent sensing, labelling and dynamic therapy [15][16][17][18]. On the other hand, SiQDs still undergo intensive research, since their fundamental photophysics is less understood than the photophysics of particles made from direct gap semiconductors [19].…”
Section: Introductionmentioning
confidence: 99%
“…An important advantage of silicon quantum dots (SiQDs) is that, unlike other elements, silicon is biocompatible. Consequently, SiQDs can be used in hot research fields of nanomedicine, such as fluorescent sensing, labelling and dynamic therapy [15][16][17][18]. On the other hand, SiQDs still undergo intensive research, since their fundamental photophysics is less understood than the photophysics of particles made from direct gap semiconductors [19].…”
Section: Introductionmentioning
confidence: 99%
“…Their two-photon luminescence platform was suitable for subsequent selective cancer cells imaging in a biological transparency window using the 960 nm wavelength light. Recent in vitro and in vivo toxicity studies demonstrated the unique biocompatibility of optimised Si QDs and fluorescent nanodiamonds, positioning them as excellent candidates for diagnostic imaging and promising non-toxic vectors for therapeutic drug delivery [22]. Composite silica-coated gold nanosphere/quantum dots nanoparticles (AueSiO2-QDs/SiO2-PVP) produced by Song et al [87] were implemented as dual mode probes for contrast-enhanced X-ray CT and fluorescence imaging.…”
Section: In Vivo Imaging Using Quantum Dotsmentioning
confidence: 99%
“…1 B, C) according to Thomson Reuters Web of Science™ database clearly reflects such "cooling down" period after 2010 resulting in a significant reduction in the initially steady exponential growth of publication rates. This trend has been partially or completely reversed by 2014 and it is intriguing whether we will see it sustained in 2015 and beyond.Such returning enthusiasm has been reinvigorated by a number of objective tendencies in the related technological developments, including the arrival of innovative nanotechnology-enabled tools for diagnostic and ex vivo imaging applications [18,19], the arrival of new types of QDs of alternative nature offering the opportunities of reducing the undesirable QDs-associated toxicity and side effects, such as carbon, graphene [20,21], silicon quantum dots and nanodiamonds [22], hence refocusing the attention of scientists pursuing the progress in this field in academia, research institutions and industry alike. Selective optimisation and surface chemistry manipulation of semiconductor QDs hold the potential for their multimodal applications such as ultrasensitive detection in diagnostic systems, as well as drug delivery approaches, combining precision targeting, drug delivery and imaging in a single assay [18].…”
mentioning
confidence: 99%
“…They possess an sp 3 hybridized core and have small amounts of graphitic carbon on the surface. Fluorescent diamond nanocrysals emit from point defects, particularly the negatively charged nitrogen vacancy site [10][11][12][13]. Unlike diamond nanocrystals, CQDs and GQDs have greater sp 2 character, which is symbolic of nanocrystalline graphite containing lower amounts of carbon with higher oxygen contents.…”
Section: Introductionmentioning
confidence: 99%